STUDIES AND RESEARCH ON POLLUTION OF ENVIRONMENTAL FACTORS IN THE AREA SC ROMPLUMB BAIA MARE FROM ANTHROPOGENICAL ACTIVITY - COCIORHAN CAMELIA SIMONA (Aerul şi Apa: Componente ale Mediului, 2011)
The main ways of soil pollution are: on path air or atmospheric path and on terrestrial path, pollution path of direct their. Sources of air pollution are two categories: natural sources (volcanic eruptions, decomposition acts, etc.) and artificial, resulting from human activities (mining and metallurgy, energy, etc.). Solid air pollutants are those treated in the paper. They are dispersed in the air from emissions of particles which containing heavy metal ions in the atmosphere having a low sedimentation rate. Finest particles, dispersed in the air gets a considerable stability, for which will persist for a much longer time in air, thereby of increasing pollution. Direct pollution comes from direct deposit of minerals on the soil as raw materials and hazardous waste, particle entrainment by deflation surface dumps, infiltration of sewage from emplacement, accidental discharge of sewage from the emplacement and crack pipes, etc. This paper shows how it is influenced soil pollution and crack pipes, etc. from the perimeter intrauzinal and extrauzinal of SC Romplumb SA by two of the factors leading to pollution, conveying technological waste water and atmospheric emissions, respectivelly.